A numerical study of the bubble induced pressure fluctuation in gas-fluidized beds - Zhang, Yuli; Xiao, Rui; Ye, Mao; Liu, Zhongmin (Powder technology, 2017)
Pressure fluctuation analysis has been widely accepted as an efficient way for bubble size estimation in fluidized beds since the local bubble induced pressure fluctuation, which is believed to be a function of bubble size, can be separated away from the global pressure waves. The spectral data decomposition method developed by van der Schaaf et al. (2002) Van der Schaaf et al. (2002) has been widely used in this regard. However, it has been found in various experimental studies that the proportionality constant between the reference data (obtained via measurements by various techniques or predicted by well-established correlations) and the estimated bubble size differs significantly in different applications. In this work we try to understand the scattered proportionality constants via a numerical study based on the Euler-Euler two-fluid model. The simulation results indicate that the local bubble induced pressure fluctuation is affected not only by bubble size, but also by the lateral distance between the rising bubble and detecting point, bubble shape, bed diameter, and bubble coalescence. Without consideration of these factors, the spectral data decomposition method is subject to large deviation for bubble size estimation. [Display omitted] •Evaluation of the traditional spectral data decomposition method•Obtain factors which dominate the amplitude of bubble induced pressure fluctuations.•Key points for improving the spectral data decomposition method•Bubble coalescence induces a kind of semi-global pressure wave.